12w+4(6-w)=5x+17

Simple and best practice solution for 12w+4(6-w)=5x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12w+4(6-w)=5x+17 equation:


Simplifying
12w + 4(6 + -1w) = 5x + 17
12w + (6 * 4 + -1w * 4) = 5x + 17
12w + (24 + -4w) = 5x + 17

Reorder the terms:
24 + 12w + -4w = 5x + 17

Combine like terms: 12w + -4w = 8w
24 + 8w = 5x + 17

Reorder the terms:
24 + 8w = 17 + 5x

Solving
24 + 8w = 17 + 5x

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 8w = 17 + -24 + 5x

Combine like terms: 24 + -24 = 0
0 + 8w = 17 + -24 + 5x
8w = 17 + -24 + 5x

Combine like terms: 17 + -24 = -7
8w = -7 + 5x

Divide each side by '8'.
w = -0.875 + 0.625x

Simplifying
w = -0.875 + 0.625x

See similar equations:

| 7x-2y=2x+9y | | -8x-28=-(6-3x) | | -85+5x+x=71 | | 12x-5y=-40 | | -3x+12-4x=5x+16 | | 4(3m+4)-(14-4m)=2[4(2+m)-(1-m)] | | 7(x+4)=-8-5x | | Ax+bx-12=-8 | | 3x-7+4x-8=20 | | k-4=-15 | | 14b-21=-12 | | p^2+28p=-33 | | 3x+12x-65=115 | | -3x+12-14x=5x+16 | | -31=2.5=4.5 | | -4y^2+16y=-180 | | 40-6x=-8(x-7)+4x | | -12=-2(u-2) | | s-7fors=8 | | -2x-35-3x=55 | | -12+=-2(u-2) | | -2v-8=-5(6v-4) | | 3g^2-84g+15=0 | | -6y+8=-8y-4 | | 9v+5/4v+7=0 | | 6x-126+3x=144 | | 5.66-15.3h=5.01-13.2h+18.5 | | 7x-10=5x-12 | | 5(1+5k)-3=-29-6k | | 28w-3=5w-0.8 | | 12-5x+2x=-8x+37 | | -5+n=1 |

Equations solver categories